Anurans of the Everglades Agricultural Area - Michelle L. Casler; Wendy M. Bear; Elise V. Pearlstine; Frank J. Mazzotti (EDIS)
This is a guide to frogs and toads in south Florida. This is document Cir 1463, one of a series in the Department of Wildlife Ecology and Conservation, University of Florida. Published December 2004.